Diverse accounting standards on disclosures of Islamic financial transactions: Prospects and challenges of narrowing gaps - Ahmed H.; Tajul Ariffin F.A.; Karbhari Y.; Shafii Z. (Emerald Group Publishing Ltd., 2024)
Purpose: Since International Financial Reporting Standards (IFRS) are not primarily meant for the accounting needs of Islamic banks, the Accounting and Auditing Organisation for Islamic Financial Institutions (AAOIFI) was established to develop specific accounting standards for Shari’ah compliance. The purpose of this paper is to assess the de jure harmonisation between the disclosure requirements of the IFRS-based Malaysian Accounting Standards (MAS) and those of the AAOIFI. Design/methodology/approach: Using Malaysia as a case study, the paper examines the extent of the de jure congruence between the IFRS-based MAS and AAOIFI’s Financial Accounting Standard No 1 (FAS1), which is considered to be one of the key disclosure standards for Islamic banks. We employ leximetrics and content analysis to analyse these accounting standards and the additional guidelines introduced by the Malaysian Accounting Standards Board (MASB) and the Central Bank of Malaysia (Bank Negara Malaysia, BNM) to identify the gaps between different tiers of MAS and FAS1. Findings: The study finds that de jure congruence between the IFRS-based MAS and AAOIFI standards has improved through the introduction of additional accounting guidelines by both the MASB and the banking regulator, BNM. However, some gaps remain between the two standards. These gaps may be difficult to completely eliminate due to differences in the fundamental principles underlying the development of both standards. Originality/value: While some studies have explored the de facto congruence between AAOIFI accounting standards and others, this paper is the first, to the best of the authors’ knowledge, to examine the de jure congruence between those standards with the IFRS-based MAS.